The Cost of Children: Differences between the Genders - Jonas Nordström (Lund University, School of Economics and Management, Department of Economics, 2009)
In this paper we estimate the opportunity cost of children. The underlying theoretical model is represented by a household production model. In the empirical analysis, we consider three different cohorts for men and women born between 1955 and 1970. For the women in the two oldest cohorts, the opportunity cost of two children is estimated to 28-29 per cent of full income, which in monetary terms is close to the estimated income difference between women employed in the public and private sector. The opportunity cost of fatherhood is generally positive, but only significantly positive for men born between 1960 and 1965.
Keywords: D13; J13; 330; Children; parenthood; opportunity cost; income loss